Professional ethics of intermediaries on the real estate market - Aleksandra Piasecka (Economic and Environmental Studies (E&ES), 2012)
Professional ethics may reduce transaction costs and improve relations between intermediaries and customers. In this article, a general overview of the basic principles of professional ethics of real estate intermediaries in Poland is provided.
Keywords: 330; real estate markets; professional ethics; real estate intermediaries; Poland